Development of graphene-based poly(lactic acid) nanocomposites - Chieng, Buong Woie (2014)
The present research aims to develop a material that having balanced properties between strength and flexibility. The plasticized poly(lactic acid)s (PLA) were prepared by melt blending technique using Brabender internal mixer. The effects of three different plasticizers, (i) Epoxidized Palm Oil (EPO), (ii) Epoxidized Palm and Soybean Oil (EPSO), (iii) poly(ethylene glycol) (PEG), and their loadings on plasticized PLA were studied. PLA plasticized with EPO, EPSO, and PEG show optimum plasticization effect at 5 wt%, 5 wt% and 10 wt% plasticizer loading, respectively. PLA plasticized with hybrid plasticizer (PEG:EPO) was also performed. Hybrid plasticizer with ratio (2:1) had good miscibility with PLA. Glass transition temperature (Tg) of the plasticized PLAs obviously decreased since plasticizer increased the chain mobility of PLA. On the other hand, a novel co-plasticization and synergistic plasticization effects of the two kinds of plasticizers were achieved in the studied PLA system. However, the major drawbacks of this plasticization were the substantial decrease in the strength and modulus of the plasticized PLAs. Hence, a plasticized PLA nanocomposite was developed to get balanced properties. The synthesized Reduced Graphene Oxide (rGO) and Graphene Nanoplatelets (xGnP) were employed as graphene-based nanofiller in this study to prepare the plasticized PLA nanocomposites. rGO was synthesized from GO using green tea extracts from Camellia sinensis as a novel reducing agent. Preliminary investigation was carried out to optimize the operation condition for graphene-based PLA nanocomposites preparation by Response Surface Methodology (RSM) coupled with Central Composite Design (CCD). The effects of variables including graphene loading, temperature, speed and time on tensile strength were examined and optimized. The prepared plasticized PLA nanocomposites exhibited a significant improvement in mechanical properties at 0.3 wt% xGnP loading. The enhancement to some extent of the mechanical properties of the plasticized PLA/xGnP nanocomposites ascribed to the homogeneous dispersion and orientation of the xGnP in the polymer matrix and strong interfacial interactions between both components. Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) results proved the enhancement of tensile strength and elongation at break. Addition of rGO into PLA and plasticized PLA substantially enhanced the stiffness and toughness without deteriorating elasticity, comparing to xGnP nanocomposites. In addition, the investigation of the thermal properties by means of Thermogravimetric Analysis (TGA) has found that the presence of rGO in the system is very beneficial for improving thermal stability of the PLA and plasticized PLA. SEM micrographs of the rGO nanocomposites display homogenous and good uniformity fracture surface. TEM images revealed that the rGO remained intact as graphene sheet layers and were dispersed well into the polymer matrix, and it was confirmed by X-ray Diffraction (XRD) result which shows no graphitic peak in the XRD pattern. Water absorption, oxygen transmission rate, water vapour transmission rate, biodegradability as well as antibacterial activity of the plasticized PLA nanocomposites, all showed improved properties with the incorporation of xGnP compared to the pristine PLA and plasticized PLAs.